An Analysis of Selected Data Practices: A Case Study of the Purdue College of Agriculture. - Line Pouchard; Marianne Stowell Bracke (Issues in Science and Technology Librarianship, 2016)
This paper describes a survey of data practices given to the Purdue College of Agriculture. Data practices are a concern for many researchers with new governmental funding mandates that require data management plans, and for the institution providing resources to comply with these mandates. The survey attempted to answer these questions: What are the characteristics of the data held by respondents? What tools do the respondents use in managing, analyzing, or manipulating their data? Where do students primarily learn research data management skills? The survey documents that there is a statistically significant difference in data holding sizes between faculty and graduate students, and that MS-Excel is still the analysis tool of choice. Results also showed that many researchers in the College were not thinking of the Libraries as a resource for data management practices, preservation, or data literacy instruction for graduate students. The survey results may inform the Libraries in developing new data services and instruction, while also highlighting the need for additional research into data practices for specific disciplinary areas or types of researchers. [ABSTRACT FROM AUTHOR]